ANALISIS STILISTIKA SENO GUMIRA AJIDARMA DALAM CERPEN REMBULAN DALAM CAPUCINO: KAJIAN POSTMODERNISME JEAN FRANCOIS LYOTARD [Seno Gumira Ajidarma’s Literary Stylistics in “A Short Story Rembulan dalam Capucino”: A Study of Jean Francois Lyotard Postmodernism] - Kahar Dwi Prihantono (Kantor Bahasa Provinsi Maluku, 2018)
The research analyzes literary stylistics of Seno Gumira Ajidarma’s short story,